Caracterización del estado nutricional de los principales "latosoles" de Costa Rica, mediante la técnica del elemento faltante en el invernadero - Martini, J.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
An attempt was made to characterize the nutritional status of the principal “latosols” of Costa Rica using the missing element technique In the greenhouse as a quick biological method oss analysis. In general these “latosols” gave the highest response to P and N, medium response to K, S and minor elements and least to Mg and Ca. When the results are analyzed by horizon it is evident that while soils and subsoils are always deficient in P and N, surface soils also tend to respond better to S and minor elements and least to Ca and Mg and subsoils respond more to K and Ca and least to S and minor elements. This suggests that both soil depth and crop root penetration may determine to some extent the nutritional deficiencies of a particular soil. In general surface soils responded less to fertilization than subsoils. The effect of climate, parent material and degree of weathering also became evident. Thus, the “latosols” from the Atlantic side with higher rainfall and no definite dry season were less deficient in N but more deficient in K and Mg. The soils from the North Pacific side with less rainfall and longest dry season and developed on calcareous materials were most deficient in N and least deficient in Ca, Mg and minor elements. The more weathered soils from the South Pacific with moderate rainfall and developed on old alluvial terraces were most deficient in Ca, S and minor elements. Soil analytical results were correlated with plan top dry weights and optimum soil nutrient levels were determined from the first derivative of the quadratic regression equation. Optimum levels for tomato plant growth were: N = 0,5 and 0,6 per cent; K = 0,6 and 0,4 me/100 g; Ca = 5,0 and 7,0 me/100 g; and Mg = 3,5 and 4,5 me/100 g for soils and subsoils, respectively. It was felt that this greenhouse biological method for assessing soil fertility gave an adequate preliminary characterization of the soil fertility status since both plant top dry weights and visual deficiency symptoms presented by tomato as indicator plant correlated well with soil analysis